An Analysis of Risk-Taking in Family Firms Listed in B3 - Gabriel Voelcker; Clea Beatriz Macagnan; Daniel Vancin (BBR: Brazilian Business Review)
This work analyses the statistical relationship between family firms and risk-taking. It seeks to contribute to the growing literature on family firms by reviewing the literature on the characteristics that distinguish them from non-family firms, aiming to innovate by approaching a less-used construct for this type of firm: risk-taking. The literature on both constructs is reviewed, using theoretical and empirical works to develop the following research hypothesis: tfamily firms are more averse to risk-taking than non-family firms. This hypothesis is tested empirically using econometrics procedures in a sample with 1188 observations from publicly traded companies listed on B3. The results indicate that the presence of family firms negatively affect risk-taking. Thus, it can be concluded that family firms seem to be less prone to risk-taking than non-family firms.